KEEFEKTIFAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS XI IPA SMA NEGERI 1 TANJUNG - Susilowati, Putri Suci; Rakhmawati, Dini; Hartini, Tri (Universitas PGRI Semarang, 2024)
The purpose of this study was to determine how effective group guidance services with sociodrama techniques are to increase the self-confidence of class XI science students at SMA Negeri 1 Tanjung. This type of research is a quantitative experiment with a True Experiment research method using a pretest posttest control group design. The samples taken were 20 students, 10 students for the experimental group and 10 students for the control group using purposive random sampling. In this study, data were obtained through research instruments in the form of a self-confidence scale and interviews. The research design used was pretest, treatment, and posttest. The treatment was carried out five times in the experimental group with an average of 69 to 86.1, an increase of 17.1. The results of the hypothesis test obtained that tcount = 100,662 were consulted with a significance level of 5% (0,05) namely 2,101. This shows that tcount = 100,662 ttable = 2,101 It was concluded that group guidance services with sociodrama techniques were effective in increasing the self-confidence of class XI science students at SMA Negeri 1 Tanjung.